Supplementing Ca salts of soybean oil to late-gestating beef cows: impacts on performance and physiological responses of the offspring - Brandão, Alice Poggi (2020)
This experiment compared the performance and physiological responses of the offspring from cows supplemented with Ca salts of soybean oil (CSSO) or prilled saturated fat (CON) during late gestation. Nonlactating, pregnant, multiparous Angus × Hereford cows (n = 104) that conceived during the same fixed-time artificial insemination protocol were assigned to this experiment. Cows were ranked by pregnancy sire (one of two sires), body weight (BW), and body condition score (BCS) on day -15 of the experiment (day 180 of gestation). Cows were then assigned to receive (dry matter basis) 415 g of soybean meal per cow daily in addition to: 1) 195 g/cow daily of CSSO (n = 52) or 2) 170 g/cow daily of CON (n = 52). Cows were maintained in two pastures (26 cows/treatment per pasture) and received daily 12.7 kg/cow (dry matter basis) of grass-alfalfa hay from day -15 to calving. Cows were segregated into 1 of 24 feeding pens three times weekly and received treatments individually from day 0 to calving. Calves were weaned on day 290 of the experiment, preconditioned for 35 d (day 291 to 325), and transferred to a feedyard, where they remained until slaughter (day 514). Cows receiving CSSO and their calves had greater (P < 0.01) plasma concentrations of linoleic acid and total ω-6 PUFA compared with CON after calving. Concentrations of immunoglobulin G in the colostrum and in calf plasma 24 h after birth were greater (P ≤ 0.02) in CSSO vs. CON cattle. Calves from CSSO cows had greater (P ≤ 0.05) expression of adipogenic (adipocyte fatty acid-binding protein and stearoyl-CoA desaturase) and myogenic (myogenic differentiation 1 and myogenin) genes in the longissimus muscle (LM) compared with CON. No treatment differences in birth BW, weaning BW, and final preconditioning BW were noted (P ≥ 0.36). Average daily gain and final BW in the feedyard were greater (P ≤ 0.05) in steers from CSSO cows compared with CON. The incidence of calves diagnosed with BRD that required a second antimicrobial treatment was less (P = 0.03) in calves from CSSO cows, resulting in reduced (P = 0.05) need of treatments to regain health compared with CON. Upon slaughter, LM area was greater (P = 0.03) in calves from CSSO cows compared with CON. Collectively, these results are indicative of programming effects on postnatal offspring growth and health resultant from CSSO supplementation to late-gestating cows. Hence, supplementing CSSO to beef cows during pregnancy might be a feasible alternative to optimize offspring productivity and welfare.